2009
DOI: 10.1021/ac9018507
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Detection of DNA Hybridization using Enzyme-Induced Metallization and a Silver Ion Selective Electrode

Abstract: Here we report on a highly sensitive potentiometric detection of DNA hybridization. The new assay uses a low-volume solid-contact silver ion-selective electrode (Ag + -ISE) to monitor the depletion of silver ions induced by the biocatalytic reaction of the alkaline-phosphatase enzyme tag. The resultant potential change of the Ag + -ISE thus serves as the hybridization signal. Factors affecting the potentiometric hybridization response have been optimized to offer a detection limit of 50 fM (0.2 amol) DNA targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Wang et al [72] reported a highly-sensitive potentiometric biosensor for detecting DNA hybridization based on monitoring the depletion of Ag + ions in the presence of AuNPs induced by the biocatalytic reaction of alkaline phosphate (ALP)-enzyme labels with a solid-contact Ag + -ISlE. The proposed method does not need to dissolve the nanocrystal tracer with H 2 O 2 or to have a preconcentration step.…”
Section: Reduction Of Metal Ions By Nanoparticle-induced Biometallizamentioning
confidence: 99%
“…Wang et al [72] reported a highly-sensitive potentiometric biosensor for detecting DNA hybridization based on monitoring the depletion of Ag + ions in the presence of AuNPs induced by the biocatalytic reaction of alkaline phosphate (ALP)-enzyme labels with a solid-contact Ag + -ISlE. The proposed method does not need to dissolve the nanocrystal tracer with H 2 O 2 or to have a preconcentration step.…”
Section: Reduction Of Metal Ions By Nanoparticle-induced Biometallizamentioning
confidence: 99%
“…The 2-μg/ml limit of detection was established using a synthetic target as in all the work summarized in Table 2, with the exception of (Wu et al 2009) where they used bacterial lysate with no PCR.…”
Section: Applicationsmentioning
confidence: 99%
“…The limits of detection given in Table 2 would be more relevant to food safety and environmental monitoring if they were extracted from experiments that used actual samples of the pathogens as in Wu et al (2009). When authors reported in Table 2 the use of food samples or cell cultures, they use them only to establish selectivity.…”
Section: Applicationsmentioning
confidence: 99%
“…Potentiometry is the branch of electroanalytical chemistry in which potential is measured under the conditions of no current flow (Eggins, 2002;Ronkainen, 2008). A DNA biosensor was developed by Wu et al (Wu, 2009) and a cell electrochemical biosensor for monitoring hydroquinone cytotoxicity on conductive polymer modified electrode surface by Wang et al were two examples of potentiometric electrochemical biosensors. Impedimetry is an ac method that describes the response of an electrochemical cell to small amplitude sinusoidal voltage signal as a function of frequency (Prodmidis, 2010).…”
Section: Classification Of Biosensorsmentioning
confidence: 99%